Współczesne oczekiwania odnośnie zawartości i jakości opisu procesów społecznych. Problem dialogu społecznego - Lymar, Natalia (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The phenomenon of social well-being is the subject of research that involves the analysis of the organization and management of social processes. In this context, the process of organizing a dialogue between society and government institutions is particularly important. The content and quality of the dialogue affect the assessment of the proposed reforms and the success of their acceptance by society.
Keywords: government institutions; social dialogue; social policy; social processes; social well-being